1990
DOI: 10.1111/j.1547-5069.1990.tb00180.x
|View full text |Cite
|
Sign up to set email alerts
|

On My Own Terms: The Redefinition of Success in Nursing

Abstract: Studies seeking predictors of success among professional women, including nurses, define "success" largely in extrinsic terms. In the findings of two studies of nurses (N = 200; N = 722), intrinsic forms of success emerge as more highly valued than externally measured achievements. Other studies of nurses and professional women show similar findings. This is argued to reflect realism about the structural obstacles and personal costs involved in vertical careers and the balancing of priorities important to wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

1991
1991
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
6
0
2
Order By: Relevance
“…Competence and motivation are other variables that influence career commitment. Buscherhof and Seymour (1990) reported that nurses valued intrinsic forms of success such as achieving competence in clinical practice. Nurses in intensive care units, medical–surgical wards, and women's health and psychiatric/mental health specialty areas were the least committed to the organization (Ingersoll et al., 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Competence and motivation are other variables that influence career commitment. Buscherhof and Seymour (1990) reported that nurses valued intrinsic forms of success such as achieving competence in clinical practice. Nurses in intensive care units, medical–surgical wards, and women's health and psychiatric/mental health specialty areas were the least committed to the organization (Ingersoll et al., 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…1996). Literature seeks to explain various contributing factors to these stereotypes, including a hierarchical structure between a doctor and a nurse that emanates from their educational backgrounds (Dahl 1992); the history and role of nursing (Giampietro & Schloton‐Elwell 1990); sex role stereotyping (Buscherhof & Seymour 1990); and media reinforcement of the nurses’ traditional image (Sheer 1994, Bird & Waterkeyn 1997). All these factors influence the public’s perception of the image of nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Altruism in clinical practice must regain importance as a criterion for distinction. Recovery of caring as the moral base of nursing will require nurses capable of supporting a balanced list of indicators of success (Buscherhof & Seymour, 1990). Rewards for individuals achieving recognition for professional activities such as advanced education, publication, and research must not de-value the sigruficance of excellence in providing direct care.…”
Section: The Ethics Of Caringmentioning
confidence: 99%